2010
DOI: 10.1111/j.1600-0447.2010.01591.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine release in ventral striatum of pathological gamblers losing money

Abstract: Our findings suggest a dopaminergic basis of monetary losses in pathological gambling, which might explain loss-chasing behavior. The findings may have implications for the understanding of dopamine dysfunctions and impaired decision-making in pathological gambling and substance-related addictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(91 citation statements)
references
References 55 publications
8
79
3
Order By: Relevance
“…Although video gaming and PG are different activities, their similarities are evident, and the same reasoning could easily be applied to PG. One future strategy to confirm the hypothesis that PG-related brain volume abnormalities are due to the vulnerability to this condition would be to carry out MRI studies investigating the relationship between brain volume abnormalities and molecular genetic features, especially dopaminergic polymorphisms thought to be related to PG (Steeves et al, 2009;Linnet et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Although video gaming and PG are different activities, their similarities are evident, and the same reasoning could easily be applied to PG. One future strategy to confirm the hypothesis that PG-related brain volume abnormalities are due to the vulnerability to this condition would be to carry out MRI studies investigating the relationship between brain volume abnormalities and molecular genetic features, especially dopaminergic polymorphisms thought to be related to PG (Steeves et al, 2009;Linnet et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Currently, no significant differences in baseline DA binding in pathological gamblers compared to HCs seem to be present but studies indicate positive correlations between DA binding and gambling severity and impulsivity (Linnet et al 2010;Clark et al 2012;Joutsa et al 2012;Boileau et al 2013). In addition, in a PET study measuring DA activity during the Iowa Gambling Task it was found that DA release in pathological gamblers was related to excitement (Linnet et al 2011) and poor performance (Linnet et al 2010). Overall these results do suggest a role for abnormal DA binding in PG but not to the same extent as that found in drug addiction (Clark and Limbrick-Oldfield 2013).…”
Section: Neurobiology Of Disordered Gamblingmentioning
confidence: 92%
“…A study by Linnet and colleagues found that problem gamblers have increased dopamine release in their ventral striatum as compared to healthy controls when they lost money in a gambling task, implying that loss still generates motivation in problem gamblers (Linnet et al 2010). Additionally, a study by Clark and colleagues found that near misses (or almost winning) in a slot machine gambling task recruited areas of the brain that respond to wins.…”
Section: Gamblingmentioning
confidence: 97%